PENINGKATAN KOMPETENSI SUMBER DAYA MANUSIA PESANTREN UMMUL QURO DALAM MENGHADAPI ERA INDUSTRI - Ratnawati, Ratnawati; Yanurianto, Yanurianto; Suryani, Lilis (LAP4B, 2026)
The Community Service Program (PKM) aims to improve the competence of human resources at the Ummul Quro Islamic Boarding School in facing the challenges of the industrial era 4.0. This study uses a qualitative approach with a participatory training method involving 45 ustadz, ustadzah, and administrative staff. The activity was carried out through a series of intensive workshops that included digital literacy, modern education management, and technology-based curriculum development. The results showed a significant increase in digital competence by 78%, understanding of modern management by 82%, and readiness to integrate technology in learning by 75%. This program makes a strategic contribution to the transformation of traditional Islamic boarding schools into adaptive and competitive Islamic educational institutions. The implications of this research strengthen the role of universities in community development through the PKM program which has a direct impact on improving the quality of national religious education.